Social media usage and disclosure of selected University of the Philippines Integrated School (UPIS) students in Diliman, Quezon City - Moralejo, Sherina V.
This study aimed to examine and describe social media disclosure among selected University of the Philippines Integrated School students in Quezon City; determine the involvement of family members in the respondents' social media usage; and discuss the respondents' perceived risks through social media disclosure. The respondents were 61 high school students who were selected through purposive sampling. This is a descriptive research that made use of the survey method and case study. This study used a research-constructed checklist and questionnaire structured with multiple choice responses for data gathering. For the case study, the researcher used open-ended questions in the interview. The results show that all of the respondents are using social media such as Facebook, Twitter, Instagram, Snapchat, Tumblr, and Youtube; and that majority of the respondents have multiple social media accounts. Social media has three major uses for respondents: education, interaction and entertainment. Majority of them disclosed personal information such as photos, identity profile, personal problems, and relationship status in social media.They also disclosed online activities such as video watching, uploading photos, playing games, browsing and social networking. Furthermore, results show that parents ranked first among family memebers in terms of involvement in their children's social media activities. It was also revealed that almost all of the respondents are aware of the possible risks in social media disclosure, yet they still disclose personal information,an indication that despite the awareness of the risks and threats, the benefits of social media outweigh its disadvantages.Moreover, cyberbullying, sexual harassments and scams are online harassments cited by a few respondents in this study. However, online harassment may not necessarily the result of social media disclosure, but due to reasons beyond the control of social media users.